Developing student worksheet (LKPD) as a problem solving to improve the critical thinking of elementary school students (Asian Journal of Educational Technology, 2023)
Problem solving skills are useful for training students to deal with increasingly complex problems. Teaching materials that have not integrated these abilities need to be used. So this study purpose to determine the process of developing problem-solving-based LKPD to improve students' critical thinking skills and determine the effectiveness of problem-solving-based LKPD. This research was Research and Development (R & D) with reference to the Borg and Gall development model. This research was be conducted in class IV State Elementary School 2Sumberejo, Kemiling Bandar Lampung with a total of 124 students consisting of class IV A, IV B, IV C and IV D. By taking samples using simple random sampling. The results of the analysis showed that LKPD based on problem solving is feasible to use, this is evidenced by the results of the validation analysis of experts 0.97, media experts 0.95, and language experts 0.96 with the "very good" category. LKPD based on problem solving is also effective for use, this is evidenced by the significant t test results and scoresn-Gain in the experimental class 0.62 category "moderate" and the control class 0.17 category "low". It can be concluded that the problem-solving-based worksheets that have been developed at State Elementary School 2Sumberejo are valid and appropriate for use in the learning process, and problem-based worksheets are effectively used to improve students' critical thinking skills in class IV Mathematics at State Elementary School in Sumberejo, Kemiling, Bandar Lampung.